Modelagem espacial da evolução do cultivo de uvas europeias na campanha gaúcha no período de 1995 a 2015 com uso de técnicas de geoprocessamento - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Originally from countries in the Mediterranean basin, the species Vitis vinifera L, known as European grapes, is now widely cultivated in our country, both for in natura consumption, as table grapes, and preferably for wine production in the South. In recent years, regions with no tradition of grape cultivation have been gaining prominence in the Brazilian scenario. These regions, such as the Campanha Gaúcha, present ideal edaphoclimatic conditions for growing European grapes for the production of fine wines. The present work has the objective of processing data, from geoprocessing techniques, of the Rio Grande do Sul Vineyard Register, elaborated by Embrapa Uva e Vinho, from 1995 to 2015, to analyze the spatial dynamics of grape growing of Vitis vinifera L, in Corede Fronteira Oeste, an area defined for the study. he work presents some factors to justify the great potential of the Gaúcha Campaign for the cultivation of European grapes, such as studies of agricultural zoning of the crop for this region, market value of the lands and favorable relief for mechanization, thus justifying this study. The application of geoprocessing techniques served as an analysis tool for a better understanding of the spatial dynamics of the grape production chain in Corede Fronteira Oeste, through the maps generated.
Keywords: Cartografia dinâmica; Viticultura; Vinhedos; Fronteira oeste; Zoneamento agrícola; Dynamic cartography; Viticulture; Vineyards; West frontier; Agricultural zoning; Vitis vinífera L; CNPQ::CIENCIAS AGRARIAS